2010
DOI: 10.3892/or_00000720
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effects of lapatinib (GW572016), a dual inhibitor of EGFR and HER-2, in combination with cisplatin or paclitaxel on head and neck squamous cell carcinoma

Abstract: Abstract. The epidermal growth factor receptor (EGFR) and a related family member, HER-2, are often overexpressed simultaneously in patients with a variety of malignant tumors, and the combination may cooperatively promote cancer cell growth and survival. Heterodimerization of EGFR and HER-2 has been known to create intense proliferative signals. Lapatinib (GW572016) is a small molecule that is administrated orally and functions as a reversible inhibitor of both EGFR and HER-2 tyrosine kinases. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 34 publications
(45 reference statements)
1
23
0
1
Order By: Relevance
“…The anti-tumor effects following HER2 blockade in ARK2 and EnCa1 xenografts were associated with increased apoptosis and decreased proliferation as has been shown in lung and head and neck carcinomas (41, 42), as well as reduced levels of signaling proteins of the PI3K and MAPK pathways. The most potent acute abrogation of p-Erk, p-Akt, p-PRAS40 and p-p70S6K was seen following dual treatment with lapatinib and trastuzumab, supporting a rationale for the synergistic inhibition of tumor growth observed.…”
Section: Discussionmentioning
confidence: 63%
“…The anti-tumor effects following HER2 blockade in ARK2 and EnCa1 xenografts were associated with increased apoptosis and decreased proliferation as has been shown in lung and head and neck carcinomas (41, 42), as well as reduced levels of signaling proteins of the PI3K and MAPK pathways. The most potent acute abrogation of p-Erk, p-Akt, p-PRAS40 and p-p70S6K was seen following dual treatment with lapatinib and trastuzumab, supporting a rationale for the synergistic inhibition of tumor growth observed.…”
Section: Discussionmentioning
confidence: 63%
“…However, there were significant differences in the response of individual tumors to lapatinib treatment, evident by the wide range of IC50 concentrations (38). Another study evaluating the combined effect of lapatinib with either cisplatin or paclitaxel found additive effects both in vivo and in vitro (40). Lapatinib reduced proliferation of HNSCC cells, but no correlation was found between expression levels of EGFR or HER2 and the anti-proliferative effects (40).…”
Section: Her2 Inhibitorsmentioning
confidence: 99%
“…To date, 20 manuscripts have been reported in the peer-reviewed literature assessing HER2 expression in HNSCC tumors (14-33). Six papers have evaluated HER2 targeting in HNSCC preclinical models, and 2 trials have been completed and reported using HER2 inhibitors for this malignancy (18, 34-40). In this review, we will evaluate the preclinical and clinical data implicating HER2 as a therapeutic target in HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…In several clinical trials, lapatinib demonstrated activity in HER2 overexpressing breast cancer patients and prolonged progression-free survival in patients with advanced, Herceptin-refractory disease (24). It also was shown that lapatinib in combination with chemotherapy agents, such as cisplatin or paclitaxel, have a synergistic antitumor effect in cancers with EGFR and HER2 amplification (25). Recently, it was reported that lapatinib can inhibit cell growth in EGFR and HER2 overexpressing esophageal cancer cell lines and the combination therapy of lapatinib with cetuximab or trastuzumab is a promising strategy in the treatment of esophageal cancer (26).…”
Section: Introductionmentioning
confidence: 99%